Effects of videotaped solutions on the transfer of problem-solving skills in mathematics at the grade seven level. - Sheldrick, Wayne. (University of Ottawa (Canada), 1995)
Mathematics is a broad field, mastered at a functional level by many preschoolers, and taught in its different forms to students from four years of age to adults in school. A review of the literature revealed a large number of instructional interventions in mathematics. Bruner (1960) has long advocated discovery learning. Collaborative learning, working with peers, was effective in developing strategies (Collins, 1992). Worked examples have been used from kindergarten (Villasenor and Kepner, 1993), to university (Schoenfeld, 1985). Allowing a student to watch a peer solving a problem on videotape combines all three types of intervention, and offers many advantages to the learner. A review of the literature did not find evidence that a videotaped intervention had previously been used in mathematics problem solving at the grade seven level. The current study was exploratory in nature, with both a quantitative and qualitative component. Three isomorphic problems were developed which were in areas of interest suggested by students at the same grade level. These problems were considered to be "real world" problems because they involved construction projects similar to ones which the students might have encountered in school or at home. The videotape of a grade seven student solving one of these problems was obtained and used as an instructional intervention. Thirty-four grade seven students were divided into six groups, three experimental and three control groups. Each of the three experimental groups received a different sequence of problems to solve, but each group saw the videotaped problem solution before solving a common final problem. One control group received the same sequence of problems as each of the experimental groups, but they did not see the video before solving the final problem. The students who viewed the video reported that watching the student on the video solve the problem did have an impact on their work. After watching the videotaped problem solution these students spent less time analyzing the next problem, suggesting that the video had resulted in the development of a mental model for this type of problem. Support for this conclusion was also found in the increased amount of time spent on Global Monitoring. These students appeared to be more aware of their global plan, and in many cases to have a better global plan. The improved global plan was demonstrated in their selection of a higher level strategy to solve the second problem. The performance of both the experimental and control groups might have been influenced by the effects of having practised on the first problem. This study found that having one problem to solve did not have a positive effect on the second problem solution for either group. Practise, combined with seeing a videotaped problem solution which was different from the one just attempted, was also not beneficial. The intervention which was most effective was the one in which the students saw the solution of the problem which they had just attempted. All of the students receiving this treatment developed a more complete global plan, and used a more advanced strategy on their second problem. Two of the six subjects solved the problem correctly when they had not been able to solve their first problem.
Keywords: Education, Mathematics.